Niqivut Silalu Asijjipalliajuq: Building a Community-Led Food Sovereignty and Climate Change Research Program in Nunavut, Canada - Amy Caughey; Pitsiula Kilabuk; Igah Sanguya; Michelle Doucette; Martha Jaw; Jean Allen; Lily Maniapik; Theresa Koonoo; Wanda Joy; Jamal Shirley; Jan M. Sargeant; Helle Møller; et al. (Nutrients, 2022)
The history of health research in Inuit communities in Canada recounts unethical and colonizing research practices. Recent decades have witnessed profound changes that have advanced ethical and community-driven research, yet much work remains. Inuit have called for research reform in Inuit Nunangat, most recently creating the National Inuit Strategy on Research (NISR) as a framework to support this work. The present study details the process undertaken to create a research program guided by the NISR to address food security, nutrition, and climate change in Inuit Nunangat. Four main elements were identified as critical to supporting the development of a meaningful and authentic community-led program of research: developing Inuit-identified research questions that are relevant and important to Inuit communities; identifying Inuit expertise to answer these questions; re-envisioning and innovating research methodologies that are meaningful to Inuit and reflect Inuit knowledge and societal values; and identifying approaches to mobilizing knowledge that can be applied to support food security and climate change adaptation. We also identify considerations for funding agencies to support the meaningful development of Inuit-led research proposals, including aligning funding with community priorities, reconsidering who the researchers are, and investing in community infrastructure. Our critical reflection on the research program development process provides insight into community-led research that can support Inuit self-determination in research, enhance local ethical conduct of research, privilege Inuit knowledge systems, and align Inuit-identified research priorities with research funding opportunities in health research. While we focus on Inuit-led research in Nunavut, Canada, these insights may be of interest more broadly to Indigenous health research.